Ciudades libres: La dramaturgia subterránea del Off-Off Broadway Neoyorquino en los años sesenta - Ana Fernández-caparrós Turina (Revista de Filología Románica, 2011)
During the Sixties there were a series of social, cultural, political and economic factors that led to the emergence of an underground theatre movement localized in New York's Greenwich Village and Lower East Side. This counter-cultural theatre was born under very specific historical conditions, (coinciding with the rise of the Civil Right's movement, the emergence of youth culture, etc.), and it only lasted for several years. Yet, its vitality would turn out to be essential in the development of contemporary American Drama in promoting the work of young playwrights such as Shepard, Wilson or Fornes, whose experimentations opened the way for future generations of dramatists. One of the key elements in order to understand the emergence and promotion of the playwright's work is the notion of community, that is, the acknowledgement of the importance of belonging to an urban community; this paper will thus explore in which ways did the urban context shape an often transgressive aesthetic experience characterized by an unconditional freedom of expression.